Indonesian Legal Readiness: Regulation of Right to be Forgotten in Relation to Big Data - Heribertus Untung Setyardi (UNIVERSITAS PGRI YOGYAKARTA, 2023)
Abstract Big Data is one of the new technological breakthroughs that marks the Industrial Revolution 4.0. Big Data has been widely used by entities in Indonesia to obtain and share data and information effectively and efficiently. In connection with this, through this paper the author intends to connect the Big Data phenomenon with the Right to be Forgotten (RBF) concept stipulated in Law No. 19 of 2016 concerning Information and Electronic Transactions, because both are related to electronic data and information. The aim is to see the compatibility between the two. In related of the matter above, it was found that the regulation of RBF in Indonesia does not seem to support the existence of Big Data. This is because RBF arrangements in Indonesia have weaknesses, including, first, the absence of rules regarding the type of information that can be requested to be removed through the RBF mechanism; second, Indonesian law cannot reach the jurisdiction of other countries if the data and information shared through Big Data technology are outside Indonesian territory; third, the absence of benchmarks to determine whether the request for removal of electronic information and data is accepted or rejected. Keywords: Big Data, Right to be Forgotten, Indonesian Law